Respostas
respondido por:
2
f(x) = 3x + 2
f(0) = 3*0 +2 f(0) = 2
f(1) = 3*1 +2 f(1) = 5
f(2) = 3*2 +2 f(2) = 8
f(0) = 3*0 +2 f(0) = 2
f(1) = 3*1 +2 f(1) = 5
f(2) = 3*2 +2 f(2) = 8
respondido por:
3
f(x) = 3x + 2
f(0) = 3.0 + 2
f(0) = 2
f(1) = 3.1 + 2
f(1) = 3 + 2
f(1) = 5
f(2) = 3.2 + 2
f(2) = 6 + 2
f(2) = 8
f(0) + (1) + f(2) =
2 + 5 + 8 =
15 < --- resposta.
f(0) = 3.0 + 2
f(0) = 2
f(1) = 3.1 + 2
f(1) = 3 + 2
f(1) = 5
f(2) = 3.2 + 2
f(2) = 6 + 2
f(2) = 8
f(0) + (1) + f(2) =
2 + 5 + 8 =
15 < --- resposta.
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás